Hepatocellular carcinoma in Gaucher disease: an international case series. Issue 5 (8th February 2018) - Regenboog, Martine; van Dussen, Laura; Verheij, Joanne; Weinreb, Neal J.; Santosa, David; vom Dahl, Stephan; Häussinger, Dieter; Müller, Meike N.; Canbay, Ali; Rigoldi, Miriam; Piperno, Alberto; Dinur, Tama; et al.
Abstract: Gaucher disease (GD) is associated with an increased risk for malignancies. Next to hematological malignancies, the development of solid tumors in several organs has been described. The liver is one of the major storage sites involved in GD pathogenesis, and is also affected by liver‐specific complications. In this case series, we describe 16 GD type 1 (GD1) patients from eight different referral centers around the world who developed hepatocellular carcinoma (HCC). Potential factors contributing to the increased HCC risk in GD patients are studied. Eleven patients had undergone a splenectomy in the past. Liver cirrhosis, one of the main risk factors for the development of HCC, was present in nine out of 14 patients for whom data was available. Three out of seven examined patients showed a transferrin saturation > 45%. In these three patients the presence of iron overload after histopathological examination of the liver was shown. Chronic hepatitis C infection was present in three of 14 examined cases. We summarized all findings and made a comparison to the literature. We recommend that GD patients, especially those with prior splenectomy or iron overload, be evaluated for signs of liver fibrosis and if found to be monitored for HCC development.